A Pilot Low-Inflammatory Dietary Intervention to Reduce Inflammation and Improve Quality of Life in Patients With Familial Adenomatous Polyposis: Protocol Description and Preliminary Results. (May 2019) - Pasanisi, Patrizia; Gariboldi, Manuela; Verderio, Paolo; Signoroni, Stefano; Mancini, Andrea; Rivoltini, Licia; Milione, Massimo; Masci, Enzo; Ciniselli, Chiara Maura; Bruno, Eleonora; Macciotta, Alessandra; Belfiore, Antonino; et al.
Patients with familial adenomatous polyposis (FAP) depend on a lifelong endoscopic surveillance programme and prophylactic surgery, and usually suffer nutritional problems. Intestinal inflammation has been linked to both FAP and colorectal cancer. Epidemiological studies show a relationship between diet and inflammation. Preventive dietary recommendations for FAP patients are so far lacking. We have designed a nonrandomized prospective pilot study on FAP patients to assess whether a low-inflammatory diet based on the Mediterranean diet principles and recipes, by interacting with the microbiota, reduces gastrointestinal markers of inflammation and improves quality of life. This report describes the scientific protocol of the study and reports the participants' adherence to the proposed dietary recommendations. Thirty-four FAP patients older than 18 years, bearing the APC pathogenic variant, who underwent prophylactic total colectomy with ileo-rectal anastomosis were eligible into the study. During the 3-month dietary intervention, they reported improvements in their consumption of Mediterranean foods (vegetables, fruits, fish, and legumes), and a reduction in pro-inflammatory foods (red/processed meat and sweets); this led to a significant increase in their adherence to the Mediterranean diet. The improvement was accompanied by a decrease in the number of diarrhoeal discharges. These preliminary results are encouraging with regard to feasibility, dietary outcome measures, and safety.